PTU-316 Has a change in bowel prep regime for diabetics improved their outcomes within the bowel cancer screening programme (bcsp). (22nd June 2015) - Taggart, N; Mbuyongha, M; Leedham, L; Lowe, G; Gibson, H; Hymer, W; Davies, D; Mumtaz-Wong, S; Sarkar, S
Abstract : Introduction: Diabetic patients (DM) often have numerous co-morbidities and can suffer from autonomic dysfunction and poor GI motility. Within the Bowel Cancer Screening Programme (BCSP) we have previously shown that using our standard regime of moviprep, that the prep was as described as inadequate in 14% patients all of which needed repeat procedures, but CIR was 92%. This was important as the adenoma detection rate (ADR) in these patients was high at 62%. 1 The bowel prep regime for diabetics was changed to Kleen Prep and this re-audit was performed to close the loop in order to determine whether this intervention was effective. Method: A re-audit was performed in over 10 months in 2014 on all diabetic patients that had Kleen prep as their primary bowel prep within the Liverpool and Wirral BCSP. The outcomes audited was the amount of inadequate prep, repeat colonoscopy procedures, ADR and Caecal intubation rate (CIR). Results: 56 patients (64% male) were audited with mean age was X. Median ASA was II. Bowel prep rating was good in 14%, adequate in 77% and inadequate in 9%. All inadequately prep patients needed a repeat procedure. This compared to just 3.65% of inadequate preps over this period. The CIR was far lower in this diabetic group was 89.3%, (One patient had a failed procedure due to looping) which compared to an overall CIR on the programme of 97.3% over this period. The ADR in the diabetic group was 55%, which compared to an ADR of 60.6%. No patients had any adverse events, readmissions or 30-day mortality. Conclusion: Following our change in regime: Bowel preparation with Kleen prep now just meets below QA &GRS standards resulting in less repeats (9% with Kleen prep verse 14% with moviprep). However, their poor bowel preparation remains a challenge as both CIR and ADR seems to be adversely affected as a consequence. Disclosure of interest: None Declared. Reference: Do diabetic patients have any worse outcomes than non-diabetic patients at colonoscopy within the bowel cancer screening programme? A Case Controlled Study- BSG, 2012